Postoperative correction of rhinolalia. (Eurasian Journal of Humanities and Social Sciences, 2025)
This article discusses the corrective actions that need to be taken after surgery for rhinorrhea speech defect. In particular, the role of speech therapy massage in the correction of rhinolalia speech defects and the use of speech therapy games in the correction of speech defects, the importance of systematization in the conduct of corrective exercises were revealed